1995
DOI: 10.1111/j.1365-3059.1995.tb02734.x
|View full text |Cite
|
Sign up to set email alerts
|

High and low pre‐inoculation temperatures decrease the effectiveness of the Lr 20 and Sr 15 rust resistance genes in wheat

Abstract: Spring wheat seedlings containing Lr20 and Srl5 resistance alleles were raised at 30°C, prior to inoculation with leaf rust (Puccinia recondita race 76-2.3) and stem rust (Puccinia graminis f.sp. tritici race 343-1.2.3.5,6) pathogens, respectively. Infected plants were then grown at one of seven temperatures in the range 18°-30° C and infection types were scored at 10 days post-inoculation. These results were compared with those obtained for plants raised at a pre-inoculation temperature of 18 °C. In both 18 C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Yet under natural conditions, temperatures are constantly changing and the effect of this on resistance needs further investigation. It is possible that other temperature-responsive resistance genes may respond to changes in temperature in a similar way to that seen in UC1041 +/- Yr36 , rather than only requiring exposure to a temperature threshold [ 10 , 23 , 24 ]. For example, a study by Broers and Wallenburg [ 12 ] observed that a decrease in temperature increases Lr34/Yr18 resistance to leaf rust, although in this study there was no negative control treatment involving plants not exposed to the temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…Yet under natural conditions, temperatures are constantly changing and the effect of this on resistance needs further investigation. It is possible that other temperature-responsive resistance genes may respond to changes in temperature in a similar way to that seen in UC1041 +/- Yr36 , rather than only requiring exposure to a temperature threshold [ 10 , 23 , 24 ]. For example, a study by Broers and Wallenburg [ 12 ] observed that a decrease in temperature increases Lr34/Yr18 resistance to leaf rust, although in this study there was no negative control treatment involving plants not exposed to the temperature change.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature dependency of the mlo gene has already been mentioned, but temperature also affects resistance to other pathogens. For example, the rust-resistance genes Lr20 and Sr15 lose effectiveness as temperature increases (Ramage & Sutherland, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In most fungal plant diseases, infection, latent period, lesion development and sporulation depend on temperature, humidity, leaf wetness duration and solar radiation (Zadoks & Schein, 1979). Several authors also mention the effect of pre‐inoculation temperature on epidemic parameters (Brown & Shipton, 1964; Ramage & Sutherland, 1995; Gijzen et al. , 1996).…”
Section: Introductionmentioning
confidence: 99%